ANTI-CORRUPTION SYSTEM FORMATION: UKRAINIAN FEATURES - Гринь, І. О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
The phenomenon of corruption is considered. The interaction of such state anti-corruption bodies as: National Agency of the Prevention of Corruption (NACP), National Anti-Corruption Bureau of Ukraine (NABU), Specialized Anti-Corruption Prosecutor's Office (SAP), National Agency of Ukraine on identification, search, and management of assets received from corruption and other crimes, the National Council on Anti-Corruption Policy under the President of Ukraine and the State Bureau of Investigation (GDB). Their authorities are analyzed, their «touch points» are defined.